Question
upstudy study bank question image url

c) \( x-\frac{1}{2}+\frac{1}{6}=\frac{1}{5}-\frac{3}{4} \)

Ask by Young Bolton. in Colombia
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

La solución es \( x = -\frac{13}{60} \).

Solution

Para resolver la ecuación   x – ½ + 1/6 = 1/5 – 3/4 realizaremos los siguientes pasos: 1. Simplificamos el lado izquierdo agrupando los términos constantes:   x – ½ + 1/6   Para operar –½ + 1/6, buscamos denominador común: 6.   –½ = –3/6  (así, –½ se expresa como –3/6)   Luego: –3/6 + 1/6 = –2/6 = –1/3   Por lo tanto, el lado izquierdo se convierte en:   x – 1/3 2. Simplificamos el lado derecho:   1/5 – 3/4   Encontramos el denominador común de 5 y 4: 20.   1/5 = 4/20  y 3/4 = 15/20   La resta es: 4/20 – 15/20 = –11/20 3. Se obtiene la ecuación simplificada:   x – 1/3 = –11/20 4. Sumamos 1/3 a ambos lados para despejar a x:   x = –11/20 + 1/3   Para sumar, buscamos denominador común: 60.   –11/20 = –33/60   y 1/3 = 20/60   Entonces:   x = –33/60 + 20/60 = –13/60 La solución es:   x = –13/60

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( x - \frac{1}{2} + \frac{1}{6} = \frac{1}{5} - \frac{3}{4} \), first simplify both sides. On the right, convert \( \frac{1}{5} \) and \( \frac{3}{4} \) to a common denominator, which is 20. Thus, \( \frac{1}{5} = \frac{4}{20} \) and \( \frac{3}{4} = \frac{15}{20} \). This gives us: \[ \frac{1}{5} - \frac{3}{4} = \frac{4}{20} - \frac{15}{20} = -\frac{11}{20} \] Now the equation looks like: \[ x - \frac{1}{2} + \frac{1}{6} = -\frac{11}{20} \] Next, simplify the left side by finding a common denominator for \( -\frac{1}{2} \) and \( \frac{1}{6} \). The least common multiple of 2 and 6 is 6. Rewrite \( -\frac{1}{2} \) as \( -\frac{3}{6} \): \[ x - \frac{3}{6} + \frac{1}{6} = x - \frac{2}{6} = x - \frac{1}{3} \] Now, we have the equation: \[ x - \frac{1}{3} = -\frac{11}{20} \] To isolate \( x \), add \( \frac{1}{3} \) to both sides. Convert \( \frac{1}{3} \) to a fraction with a denominator of 60 for easier adding: \[ \frac{1}{3} = \frac{20}{60} \quad \text{and} \quad -\frac{11}{20} = -\frac{33}{60} \] Thus: \[ x = -\frac{33}{60} + \frac{20}{60} = -\frac{13}{60} \] Therefore, the solution is: \[ x = -\frac{13}{60} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy